Research of training methods for serving technique in young volleyball players - Yin Yining (Theory and Practice of Physical Culture, 2025)
Purpose of the study: to study the methods of teaching the technique of serving the ball to young volleyball players. Methodology and organization of the study: The research material includes sources that analyze the serving skills of young volleyball players. These sources analyze the development of serving skills from both a theoretical and methodological point of view. In addition, direct observation of the training of young volleyball players in Henan Province was also conducted. The work uses methods of analysis of theoretical sources, direct pedagogical observation, and methodological development of own recommendations. The practical significance of the research is high. Its results may be useful for volleyball coaches, methodologists of sports schools, sports psychologists, as well as for a wide range of interested parties. Research results and conclusions: The prospects of the research consist in identifying new methods of forming the serving technique of young volleyball players, as well as in positive changes in existing methods. The article briefly outlines the important role of psychological factors that influence the serving technique of young volleyball players. Perhaps, in the future, it will be possible to study the psychological component of children’s and youth volleyball in more detail, not only in the context of serving, but also in a broader aspect of training and competitive activities of young volleyball players.